The Big Book of UFOs by Chris A. Rutkowski - Cox, Billy (Journal of Scientific Exploration, 2013)
You don’t need to wander very far into Chris Rutkowski’s aptly named The Big Book of UFOs to get the message: The guy knows his stuff. He’s got it in chronological order, from pre-20th century trends all the way up to the double-aughts of the 21st. He’s got it broken down into narrow categories: contactees, abductees, implants, hybrids, hoaxes, debunkers; you name it, this 396-page tome likely has a reference. Much of the material, such as Roswell and SETI, is so familiar that you don’t even have to be a hardcore student of the genre to recognize it. But some entries are so arcane it’s doubtful that even Jeopardy-caliber UFO nerds could pass the test. Category: The 1890s Wave. Answer: During the Teddy Roosevelt Administration, sightings of unknown “airships” became so common that this company took out newspaper ads with graphic UFO illustrations stating “This Is What You Saw,” accompanied by the slogan “High up in quality, low in price.” Question: What is White Star Baking Powder? On the other hand, Rutkowski’s sojourns into remote corners of the world could also prepare us for some future Geography category competition. There were the miners who saw triangular lights outside Taparko, Burkina Faso, on Christmas night, 2005. The following year, at Port el Kantouni, Tunisia, a couple of people reported seeing low-flying rods with running lights. Some encounters are more unfortunate than others. A dog dies in Uruguay from internal bleeding in 1977 as a possible result of exposure to UFO radiation. The same year, a Polish resident of Piastow suffers headaches and faceburn after an alleged encounter. In 1975, a fellow living near Macheke, Rhodesia, is thrown to the ground and rendered unconscious when struck by a “bright white beam of light” outside his house.